Formulation fusion event: a hands-on approach to learning formulations / Nurul Alyaa Ibrahim - Ibrahim, Nurul Alyaa (Faculty of Pharmacy, 2025)
On 6th and 7thJanuary 2025, the Formulation Fusion: From Lab-toShowcase Event was successfully organised as part of the PHD211: Semi-Solid Dosage Forms course at UiTM Bertam Campus. This event was conducted by Ms. Alyaa, with the support of two distinguished lecturers, Dr. Wong Yuet Yen and Dr. Mohd Nadzri, as well as two pharmacist assistants, Mr. Faiz and Ms. Isfariena. This event involved event involved Semester 3 Diploma in Pharmacy students, providing them with a hands-on learning experience that combined both laboratory practice and scientific communication. The aim for this event was to enhance students’ compounding proficiency, encourage them to make informed decision in formulations and foster creativity in presenting pharmaceutical formulations. The Formulation Fusion event was structured into two key activities; (1) preparing products in the laboratory and creating formulations which were then translated into infographics and (2) an oral presentation session.